Evaluating effects of training within a company : methods, problems and one application - Gelderblom, Arie [Verfasser]; Koning, Jaap de [Verfasser] (My University, 1996)
"In the Netherlands, interest in the measurement of the effects of training has increased. In most cases this measurement has been done by drawing conclusions on analyses with samples of firms. However, individual companies will be more interested in the effects of training within their own organisation. In this paper we discuss possible methods of measuring the effects of training within an organisation. A crucial element of such an analysis is the use of performance indicators of individual workers. A first application of such a method in the Civil Service shows positive effects of training. However, the size of the effects should not be overrated." (author's abstract, IAB-Doku) ((en)) Die Autoren analysieren mit niederländischen Daten, wie sich innerbetriebliche Weiterbildungsmassnahmen auf die Leistung und Produktivität der Teilnehmer auswirkt und wie dies gemessen werden kann. (IAB)
Keywords: S 5.3 Personalentwicklung; G 1.3.1.2 Weiterbildungsmarkt; L 6.2.3 Evaluation; I 2.2.1 Westeuropa; Betriebliche Weiterbildung; Auswirkung; Wirkungsforschung; Produktivität; Quantitative Angaben; Niederlande